ANALISIS KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) WISATAWAN DALAM UPAYA PENGELOLAAN WISATA PENDAKIAN GUNUNG PUNDAK, TAMAN HUTAN RAYA RADEN SOERJO - Nabela, Risma Nur Laili Salma; Rinjani, Richella Ramadhani Alam; Agustina, Ana; Supriyadi, Supriyadi; Fatma, Hilda Nuzulul (Kepariwisataan: Jurnal Ilmiah, 2024)
AbstractAnalysis of tourists' willingness to pay in efforts to manage Mount Pundak climbing tourism was carried out to find out how much or maximum tourists paid for natural tourism climbing Mount Pundak. Mount Pundak is one of the areas managed by the Raden Soerjo Grand Forest Park so it is still part of a conservation area. This research aims to identify the socio-economic characteristics of tourists on Mount Pundak climbing tours, to determine tourists' willingness to pay the entry ticket price for Mount Pundak climbing tours and what factors influence the willingness to pay of tourists on Mount Pundak climbing tours. The influencing factors were analyzed using multiple linear regression analysis with the SPSS program and using the Contingent Valuation Method (CVM) analysis technique. The research results show that the majority of male tourists are students with an income level of < IDR 1,000,000. Based on the results of the analysis of the calculation of the average Willingness to Pay value, the results obtained were IDR 15,920 per individual per visit and the factor that influenced the Willingness to Pay value was attractiveness.Keywords: Contingent Valuation Method; Mount Pundak; Tahura Raden Soerjo; Willingness to PayAbstrakAnalisis kesediaan membayar (Willingness to Pay) wisatawan dalam upaya pengelolaan wisata pendakian Gunung Pundak dilakukan untuk mengetahui seberapa besar atau maksimum yang wisatawan bayarkan untuk wisata alam pendakian Gunung Pundak. Gunung Pundak merupakan salah satu kawasan yang dikelola oleh Taman Hutan Raya Raden Soerjo sehingga masih menjadi bagian kawasan konservasi. Penelitian ini bertujuan untuk mengidentifikasi karakteristik sosial ekonomi wisatawan wisata pendakian Gunung Pundak, untuk mengetahui kesediaan membayar wisatawan terhadap harga tiket masuk wisata pendakian Gunung Pundak dan faktor apa saja yang mempengaruhi kesediaan membayar wisatawan wisata pendakian Gunung Pundak. Faktor-faktor yang mempengaruhi dianalisis menggunakan analisis regresi linier berganda dengan program SPSS dan menggunakan teknik analisis Contingent Valuation Method (CVM). Hasil penelitian menunjukkan bahwa mayoritas wisatawan berjenis kelamin laki-laki berstatus pelajar dengan tingkat pendapatan < Rp 1.000.000. Berdasarkan hasil analisis perhitungan nilai rata-rata Willingness to Pay diperoleh hasil sebesar Rp 15.920 per individu per kunjungan dan faktor yang mempengaruhi nilai Willingness to Pay adalah daya tarik.Kata Kunci: Contingent Valuation Method; Gunung Pundak; Tahura Raden Soerjo; Willingness to Pay